Comparative analysis of the seminal plasma proteomes of oligoasthenozoospermic and normozoospermic men. Issue 5 (May 2015) - Giacomini, Elisa; Ura, Blendi; Giolo, Elena; Luppi, Stefania; Martinelli, Monica; Garcia, Rodolfo C.; Ricci, Giuseppe
Abstract A comparative proteomic study of oligoasthenozoospermic and normozoospermic seminal plasmas was conducted to establish differences in protein expression. Oligoasthenozoospermia (when semen presents with a low concentration and reduced motility of spermatozoa) is common in male infertility. Two-dimensional protein maps from seminal plasma samples from 10 men with normozoospermia and 10 men with idiopathic oligoasthenozoospermia were obtained by isoelectric focusing followed by sodium dodecyl-sulphate polyacrylamide electrophoresis. Map images were analysed using dedicated software involving normalization, spot-to-spot volume comparison and statistical treatment of the results to establish the significance of differences between normal and oligoasthenozoospermic samples. Six out of 1028 spots showed over 1.5-fold relative intensity differences (P < 0.05, analysis of variance). Four proteins were identified by nano liquid chromatography-electrospray ionization-mass spectrometry/mass spectrometry of their tryptic peptides and database searches. Two proteins were more than three-fold under-expressed in oligoasthenozoospermia, namely epididymal secretory protein E1 and galectin-3-binding protein; the other (lipocalin-1 and a prolactin-inducible protein form) were over-expressed. The identity and differential expression of epididymal secretory protein E1 was verified by Western-blotting. The statistically significant differential expression of these four proteins in oligoasthenozoospermia compared with normozoospermia provides a molecular basis for further investigations into the pathogenic mechanisms underlying idiopathic oligoasthenozoospermia.